What do we say when we say 'Juan Gelman'? On pseudonyms and polemics in recent Argentine poetry - Bollig, B (Modern Humanities Research Association, 2014)
Juan Gelman is perhaps Argentina's best-known living poet, a Cervantes Prize winner and a name mentioned annually in literary circles as a Nobel candidate. The question explored here is at once simple and complex: why do polemics and polemicists seem attracted to Gelman? he article seeks an answer in Gelman's poetry, focusing on a long-standing tendency in his work, namely his publication of poems under names other than his own, and the links between his pseudonymous poetry and apocryphal translations and political shifts in his work.